Digital Marketing Strategy for Snack MSME (Micro, Small and Medium Enterprises) Landbutter Bakery during The Covid-19 Pandemic - Hadi, Belani Asmara; Pratminingsih, Sri Astuti (Proceedings International Conference on Education Innovation and Social Science, 2023)
Snack MSME (Micro, Small and Medium Enterprises) business unit categories are currently one of the most promising to grow. The objective of this research was to develop digital marketing strategies for Landbutter Bakery, a Snack MSME (Micro, Small and Medium Enterprises) located in Bandung City, West Java, Indonesia. The study employs a qualitative descriptive approach to explore Landbutter Bakery's digital marketing strategies in promoting their products during the Covid-19 pandemic. The data analysis follows the Miles and Huberman method, involving several stages including data collection, data presentation, data reduction, and drawing conclusions in an interactive process. The results of the study show that, first, the implementation of the "Finest Food Delight" branding is an integral aspect of Landbutter Bakery's digital marketing strategy aimed at attracting an increase in customer orders., this is supported by qualitative analysis using the Miles and Huberman method (1994). Second, the process of digital marketing involves conducting online marketing activities and implementing 8 (eight) stages of content marketing. (Kotler, 2017). Third, social media as a digital marketing strategy has been quite successful in boosting the growth of customer's orders of Landbutter Bakery's products.